Ponarejena zdravila v teoriji in praksi (University of Maribor Press, 2019)
Counterfeit Medicines in Theory and Practice. Counterfeit medicines are a serious global issue triggering a clearly disparate response in different countries. Often, a question arises as to whether the general population is actually aware of the existence of counterfeit medicines, their consequences and the damage they cause. Statistical data and individual cases indicate that crime related to counterfeit medicines is increasing and that the investigation of such crime is complex and often transnational. Furthermore, it is strongly indicated that the profits are extremely high. The present monograph provides both theoretical and practical insights into this complex phenomenon. It offers solutions to certain issues regarding the detection and, investigation of such crimes, as well as the taking of evidence. The prevention of counterfeiting medicines is also presented and discussed in several chapters. The main aim of this monograph is to highlight the importance of raising awareness about the issue of counterfeit medicines.